Building Information Modelling Execution Plan (BEP): A comparison of global practice - Ahmad Ridzuan, Abu Bakar; Ahmad Tarmizi, Haron; Rahimi, A. Rahman (Penerbit Universiti Malaysia Pahang, 2020)
Building Information Modelling (BIM) is a process supported by technologies involving the development and management of 3D digital information model representations of functional and physical of the design. To implement BIM in a project, BIM Implementation Plan or BIM Execution Plan (BEP) must be developed as a planning and monitoring strategy document. Several BEPs have been developed around the world since 2010. However, a BEP should be tailored to the type of project, stakeholder requirement, and project objectives because a comprehensive BEP is a key factor for BIM implementation success. Also, a proper BEP helps stakeholders understand and achieve the underlying objectives in using BIM. In other words, understanding the strategic framework of BEPs is important. Hence, this study identifies and compares the key elements in existing BEPs. To accomplish that aim, twenty BEPs were identified and analysed through the directed content analysis technique. This study provides a benchmarked reference for industry players on existing BEPs. Through a clear description, all parties can understand the requirements in a BEP. Based on the findings and discussions on the twenty (20) samples, BEP is a strategic planning and monitoring document used to ensure that all project deliverables are completed according to the project goals. The document framework shall include the work process, type of information, standard requirements, data exchange process, and roles and responsibilities to develop the project team members' understanding. The framework can guide the project team or stakeholders to identify the key elements and outline contents included in BEP documents. Also, researchers can use the findings for further development and improvement of existing BEPs. Understanding BEPs will ensure better BIM implementation in practice.